Diagnostic study of Cryptosomiasis in the gall bladder of some ruminant’s species in Wasit Province, Iraq - Hussein, Yasmin ghani; Alkhanaq, May naji (Journal of Neonatal Surgery, 2025)
The current study aimed to determine the prevalence of Cryptosporidium spp. in gallbladder fluid samples collected from cattle and sheep in Wasit Governorate, Iraq. Using the modified Ziehl-Neelsen stain technique, the presence of oocysts of the parasite was confirmed microscopically, showing spherical forms that ranged in color from pink to bright red. A total of 300 samples (150 from cattle and 150 from sheep) were examined between July 1, 2024, and October 30, 2024. The results revealed an infection rate of 30% in cattle and 8% in sheep. Additionally, younger animals, particularly calves under one year of age, exhibited higher infection rates due to weaker immune systems and overcrowded rearing conditions. The results also showed no significant difference in infection rates between rural and urban areas for both cattle and sheep, indicating common environmental risk factors such as water contamination and poor waste management. Statistical analysis revealed that infection rates varied with age, with younger animals being more susceptible. These findings emphasize the need to raise health awareness among farmers, improve livestock management practices, and implement advanced diagnostic techniques to reduce the spread of Cryptosporidium spp. This study contributes to the understanding of the epidemiology of cryptosporidiosis in livestock and highlights its potential as a zoonotic disease.